Pulsed field ablation for atrial fibrillation: a comprehensive bibliometric analysis of research trends and emerging Frontiers - Li, Li; Xie, Bin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) is the most prevalent cardiac arrhythmia worldwide, posing significant health burdens. Pulsed field ablation (PFA) is an emerging non-thermal technique that is gaining traction due to the ability to selectively target myocardial cells and minimize damage to surrounding tissues. We conducted a comprehensive bibliometric analysis of PFA use in AF treatment to map research trends, collaborations, and future directions.MethodsWe extracted data from the Web of Science Core Collection on September 6, 2024, using search terms related to PFA and AF. Publication trends, citation trajectories, collaborative networks, and keyword co-occurrences were analyzed utilizing tools such as Bibliometrix R, VOSviewer, and CiteSpace.ResultsIn total, 217 publications were retrieved. The number of publications increased rapidly from 2019 to 2024, with a notable surge occurring after 2022. Contributions from the United States, Germany, and China accounted for more than 60% of all publications. The institution with the largest output was The Icahn School of Medicine at Mount Sinai. The most productive journals were Europace and the Journal of Interventional Cardiac Electrophysiology. Prolific authors were identified, underscoring significant international collaborations. The most cited publications highlighted the efficacy and safety of PFA. Keywords with strong recent citation bursts included “tissue”, “cardiomyopathy”, and “closed chest ablation”.ConclusionPFA is becoming established as a viable alternative for AF ablation, showing promising safety and efficacy. This bibliometric analysis confirmed the growing scientific interest and collaborative efforts in this field, suggesting that robust future developments will occur.